Kajian Kesarjanaan Tafsir Indonesia: : Analisis Perbandingan Cara Kerja Islah Gusmian, Ervan Nurtawab, dan Jajang A. Rohmana - Fadhliyah, Lia (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2024)
This article discusses the differences in the scholarly approaches of three major Indonesian tafsir scholars, namely Islah Gusmian, Ervan Nurtawab, and Jajang A. Rohmana, within the scope of Indonesian exegetical scholarship. As prominent figures in the field of Indonesian Qur'anic interpretation, these three scholars possess unique characteristics that are often overlooked by the current generation. By analyzing and extracting data from their works, as well as from other exegetical scholars, the author aims to identify the major themes, methods, and arguments constructed by them. This exploration is significant in revealing the scholarly substance of each figure. The argument in this article posits that a researcher’s approach is shaped not only by diverse social and educational backgrounds but also by distinct patterns that they develop in discussing and expanding Indonesian tafsir studies. This is evident in how each scholar positions themselves and formulates their viewpoint in understanding the tafsir audience. This paper is expected to contribute to the mapping of their works for future researchers and serve as a literature review for a more in-depth study of Indonesian Qur'anic interpretation.